Situation Report: Romania, 28 January 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu's 70th Birthday / by Paul Gafton Religious Elements in the Glorification of Ceausescu / by Dan Ionescu Poems for Elena Ceausescu / by Dan Ionescu The Dispute with Hungary over Transylvania Most-Favored-Nation Trade Status Once More under Discussion The Romanian Cinema in the Ceausescu Era / by Crisula Stefanescu